Análisis de la ciberseguridad a la infraestructura tecnológica de la universidad técnica de Cotopaxi. - Alvarado Llano, Washington Orlando (2019)
Cybersecurity is a very important asset within a company because it deals mainly with the care of computer systems, that is why today in Ecuador companies decide to implement tools that can determine the level of vulnerability that exists within its technological infrastructure, with the aim of preventing possible cyber-attacks or information theft. In this sense, this research was developed around the use of interviews and surveys to the systems department, teachers and students, in order to have a sample of the shortcomings that the institution has in terms of Cybersecurity, also obtained bibliographic references were obtained in books, Internet and other media for familiarization in the present research. As for the research methods, it has been guided by the Hypothetical-Deductive method since it allows us to know the origin of the problem, starting from the most general to the specific, for a better understanding of the subject and each one of its derivatives. This research was carried out based on the ISO/IEC 27032/2012 standard, a new safety standard that protects the information of existing risks in cyberspace, allowing us to fully comply with the objectives set and provide possible recommendations altogether with the results of the analysis performed.